Critical velocity in the transverse passages of a railway tunnel rescue station with semi-transverse ventilation. (October 2019) - Zhou, Yuanlong; Bi, Haiquan; Wang, Honglin; Lei, Bo
Highlights: Critical velocity in the transverse passages is important for ensuring the safety of evacuated passengers. Semi-transverse smoke exhaust is advantageous over longitudinal ventilation. Numerical simulation and scaled model tests conducted to find critical velocities. Critical velocities dependent on fire source relative to passage and exhaust shaft. Abstract: In the event of a railway tunnel fire, rescue stations are intended to provide a safe, smoke-free refuge for evacuated passengers. Rescue stations are required for railway tunnels longer than 20 km. Located near the middle of the tunnel, evacuated passengers access the rescue station through a series of transverse passages. Under such emergency conditions, railway tunnel systems operate under longitudinal, transverse, or semi-transverse mechanical ventilation modes to draw in fresh air and exhaust the smoke through the top or end of the tunnel. A minimum flow velocity is required during ventilation to prevent smoke from entering the transverse passages leading to the rescue station. This critical velocity in the transverse passages is important for ensuring the safety of evacuated passengers and differs depending on the tunnel system's mode of ventilation. In this study, we used both experimental and numerical methods to investigate the critical velocity in the transverse passages with a semi-transverse ventilation mode at the railway tunnel rescue station. We constructed a 1:20 scale model of a railway tunnel system to support experimentation and used numerical simulations to determine the dependence of the critical velocity in the transverse passages on the fire source position and heat release rate, semi-transverse smoke exhaust velocity, height and width of the protection door, and tunnel blockage ratio. The results indicated that the critical velocity in the transverse passages is dependent upon the fire source position, semi-transverse smoke exhaust velocity, height of the protection door, and tunnel blockage ratio. These findings are inconsistent with previously reported findings for railway tunnel systems operating under a longitudinal ventilation mode.